1997
DOI: 10.1038/sj.onc.1201071
|View full text |Cite
|
Sign up to set email alerts
|

Tec tyrosine kinase links the cytokine receptors to PI-3 kinase probably through JAK

Abstract: Tec/Btk tyrosine kinases are members of a subgroup of Src tyrosine kinase family. They are reported to be activated in response to cytokines, such as IL-3 and IL-6. Janus kinases (JAKs) are known to associate with certain cytokine receptors, e.g. gp130, the signal transducing subunit of IL-6 receptor, and the common b chain of IL-3 receptor, which can be activated upon receptor dimerization in response to cytokines. Here we show the association between Jak1/Jak2 and Tec or Jak1 and Btk. Furthermore, Jak1 but n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(61 citation statements)
references
References 60 publications
3
57
1
Order By: Relevance
“…Further, it has been shown that the rGH signal can be transmitted to the actin cytoskeleton via Jak, p125 FAK , and tensin, and the actin polymerization produced by GH stimulation occurs due to the PI-3 kinase activation (41). Moreover, it has been suggested the indirect association of Jak2 with p125 FAK occurs via Tec and PI-3 kinase (41,50,51). In the present study we found that the physical association between Jak2 and p125FAK could be mediated via STAT3.…”
Section: Discussionsupporting
confidence: 52%
“…Further, it has been shown that the rGH signal can be transmitted to the actin cytoskeleton via Jak, p125 FAK , and tensin, and the actin polymerization produced by GH stimulation occurs due to the PI-3 kinase activation (41). Moreover, it has been suggested the indirect association of Jak2 with p125 FAK occurs via Tec and PI-3 kinase (41,50,51). In the present study we found that the physical association between Jak2 and p125FAK could be mediated via STAT3.…”
Section: Discussionsupporting
confidence: 52%
“…Btk interacts with the TIR domain of TLRs as well as with downstream molecules such as MyD88, MAL, and IL-1R-associated kinase-1, but the precise nature of these interactions is not well defined. Btk is probably activated through Src kinases although other tyrosine kinases such as PI3K and Jak1 have also been shown to phosphorylate members of the Btk family (23). Because FAK has been demonstrated to be an upstream activator of Bmx/Etk in endothelial cells (24), it is conceivable that FAK might lead to the recruitment of MyD88 via the activation of a member of the Btk family of kinases and further downstream signaling to MAPKs, AP-1, and NF-B.…”
Section: Discussionmentioning
confidence: 99%
“…Upon cytokine stimulation, Tec associates with gp 130, a signal transducer of the IL-6 family (Matsuda et al, 1995), and c-kit (Tang et al, 1994). Furthermore, it has been revealed that Tec links cytokine receptors to phosphatidylinositol 3-kinase through JAKs (Janus kinases) (Takahashi-Tezuka et al, 1997). Thus, it is highly possible that Tec plays an important role in cytokinemediated signalings.…”
Section: Introductionmentioning
confidence: 99%